The Tengmalm’s owl Aegolius funereus (Aves, Strigidae) as the definitive host of Sarcocystis funereus sp. nov. (Apicomplexa) - Máca, Ondřej; Kouba, Marek; Langrová, Iva; Panská, Lucie; Korpimäki, Erkki; González-Solís, David (Frontiers in Veterinary Science, 2024)
The present study focused on elucidating the identity, potential intermediate host, and complete life cycle of the found Sarcocystis through experimentally infected rodents. The developmental stages' morphological and molecular characterizations (28S rRNA gene, ITS1 region) are presented herein.In total, 21 Tengmalm's owl carcasses (15 nestlings, 5 fledglings, and 1 adult male) were collected in Kauhava (west-central Finland) and parasitologically examined by wet mounts.Intestinal mucosa scrapings were used to isolate oocysts/sporocysts and employed for experimental infections in dexamethasone-immunosuppressed BALB/cOlaHsd mice. Additionally, sarcocysts were searched in the skeletal muscle of 95 samples from seven wild small mammal species. All these developmental stages were molecularly characterised by the 28S rRNA gene and ITS1 region.Experimental infections were carried out by using immunosuppressed female 8-week-old BALB/cOlaHsd mice, divided into three groups: 1) water with 15 µg/ml of dexamethasone, 2) water with 30 µg/ml of dexamethasone, 3) no dexamethasone treatment. Each group consisted of four individuals. In each group, two mice were infected with 1000 sporocysts each, and the remaining two with 10000 sporocysts each. All mice were euthanised on specific days postinfection.The intestinal mucosa of 11 nestlings and 5 fledglings of the Tengmalm's owl were positive for Sarcocystis funereus sp. nov. The adult male owl and all owls' breast and heart muscles were negative for Sarcocystis. Two dexamethasone-immunosuppressed BALB/cOlaHsd mice (group 2) were positive to S. funereus sp. nov. in diaphragm and leg muscles after 22-and 24-day post-infection. Some sarcocysts were found in the wild small mammals. Molecular identification at 28S rRNA revealed sequences from naturally infected Tengmalm's owls, as well as sarcocysts of dexamethasone-immunosuppressed BALB/cOlaHsd mice were 99.87-100% similar to Sarcocystis sp. isolate Af1 previously found in the Tengmalm's owl. At the ITS1 region, the S. funereus sp.nov. isolates Af2 haplotype B and Af3 haplotype A were 98.77-100% identical to Sarcocystis sp. isolate Af1. The sequences from sarcocysts of naturally infected wild small mammals were 75.23-90.30% similar at ITS1 region to those of S. funereus sp. nov.The morphological and molecular characterisations and phylogenetic placement of S. funereus sp. nov. are presented here for the first time and support the erection of the new species.